Climate Change as a Threat Multiplier: How Environmental Degradation Fuels Conflict in the Sahel - Emmanuel, Joseph; Zacharia, Rahila Elisha (Darul Yasin Al Sys, 2025)
The Sahel region, a vast expanse just south of the Sahara Desert, has emerged as a critical nexus where climate change and insecurity converge. This opinion paper explores how climate change acts as a threat multiplier in the region, exacerbating entrenched vulnerabilities such as poverty, weak governance, ethnic divisions, and competition over diminishing natural resources. Environmental degradation manifested through desertification, drought, and water scarcity has undermined traditional livelihoods, spurred internal displacement and cross-border migration, and intensified violent conflicts, particularly between pastoralist and farming communities. These dynamics have been further exploited by extremist groups and non-state actors who capitalize on ecological stress and governance failures to recruit members, consolidate territorial control, and challenge state legitimacy. Although regional and international stakeholders, including ECOWAS, the African Union, the United Nations, and donor organizations, have initiated climate and security interventions, many efforts remain fragmented, reactive, and poorly coordinated. This paper calls for a strategic shift toward proactive, climate-sensitive peacebuilding that prioritizes inclusive resource governance, fosters regional collaboration, and strengthens grassroots resilience. Addressing the climate-security nexus in the Sahel demands urgent, integrated, and multi-level action to mitigate further destabilization and promote sustainable peace.